2009
DOI: 10.1177/0898264308328929
|View full text |Cite
|
Sign up to set email alerts
|

Assisted Living Pilot Program

Abstract: Objectives. Assisted living programs demonstrate variation in structure and services. The Department of Veterans Affairs funded this care for the first time in the Assisted Living Pilot Program (ALPP). This article presents resident health outcomes and the relationship between facility characteristics and outcomes. Method. This article presents results on 393 ALPP residents followed for 12 months after admission to 95 facilities. Results. A total of 19.8% residents died, and the average activities of daily liv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 10 publications
1
13
0
Order By: Relevance
“…Regarding facility-level predictors of placement, our findings are similar to previous U.S. studies (Dobbs et al, 2006; Hedrick et al, 2009; Phillips et al, 2003; Zimmerman et al, 2005) in that only a few facility characteristics were associated with LTC placement. Specifically, residents receiving care in facilities with larger numbers of spaces (i.e., > 30 DAL or > 148 total), LPN and/or RN coverage on-site 24/7, and/or an affiliated primary care physician showed a significantly reduced risk of LTC placement over one year.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Regarding facility-level predictors of placement, our findings are similar to previous U.S. studies (Dobbs et al, 2006; Hedrick et al, 2009; Phillips et al, 2003; Zimmerman et al, 2005) in that only a few facility characteristics were associated with LTC placement. Specifically, residents receiving care in facilities with larger numbers of spaces (i.e., > 30 DAL or > 148 total), LPN and/or RN coverage on-site 24/7, and/or an affiliated primary care physician showed a significantly reduced risk of LTC placement over one year.…”
Section: Discussionsupporting
confidence: 90%
“…Findings regarding the availability of an RN and risk of nursing home placement have been inconsistent with one study showing a reduced risk similar to ours (Phillips et al, 2003 ); another, an increased risk (Zimmerman et al, 2005 ); and others, no association (Dobbs et al, 2006 ;Hedrick et al, 2009 ). This inconsistency may refl ect the importance of staffi ng intensity and skill mix (e.g., proportion of total directcare hours provided by licensed staff) rather than simply the presence or absence of an RN (Stearns et al, 2007 ).…”
Section: Continuedmentioning
confidence: 75%
See 1 more Smart Citation
“…The data shows that +CP communities exhibited a nearly 40% lower average hospitalization rate than the –CP communities (33.8% versus 73.6%). Several senior living outcomes studies by Zimmerman et al and Hedrick et al reported average annual hospitalization rates of 51% and 40%, respectively [ 29 , 58 ]. The +CP communities exhibited hospitalization rates that were 18% and 7% lower than the averages reported by Zimmerman and Hedrick et al, respectively [ 29 , 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous pilot studies by the VA concerning the feasibility of assisted living facilities demonstrated that they were much costlier than other types of care [17,32,36,35,46]. However, these studies were conducted on a client population that had an average age of 69.3 years whereas the median age of a returning OIF/OEF veteran is 25 years old [73].…”
Section: Rationale For the Assisted Living Neurorehabilitation Pilot mentioning
confidence: 99%